Suitability of textile dyeing effluents for germinaion and seedling growth of yard long bean (Jahangirnagar University Journal of Biological Sciences, 2016)
Textile Dyeing effluents from seven different stages of dying process were used for irrigation of the pot culture of yard long bean. Maximum germination was found at 6th day of observation and the highest germination rate occurred for treatments with 2nd wash after soaping stage, which was statistically identical with the ground water treatment. Treatment 2nd wash after soaping stage showed the highest germination energy and relative germination rate consequently has the lowest germination injury rate. Treatment 2nd wash after soaping stage also produced the highest shoot length. So the effluent produced from the 2nd wash water after soaping can be used for irrigation of yard long bean.Jahangirnagar University J. Biol. Sci. 3(1): 55-65, 2014 (June)